Double‐blind, randomized, phase 2 trial of maintenance sunitinib versus placebo after response to chemotherapy in patients with advanced urothelial carcinoma. Issue 5 (18th November 2013) - Grivas, Petros D.; Daignault, Stephanie; Tagawa, Scott T.; Nanus, David M.; Stadler, Walter M.; Dreicer, Robert; Kohli, Manish; Petrylak, Daniel P.; Vaughn, David J.; Bylow, Kathryn A.; Wong, Steven G.; Sottnik, Joseph L.; et al.
Abstract : BACKGROUND: Angiogenesis contributes to the progression of urothelial carcinoma (UC). In the current study, the authors investigated the role of maintenance sunitinib in patients with advanced UC. METHODS: Patients with locally recurrent/metastatic UC and adequate organ function who achieved stable disease or a partial or complete response after 4 to 6 chemotherapy cycles were randomized to sunitinib at a dose of 50 mg/day (28 days on and 14 days off) or placebo. The primary endpoint was the 6‐month progression rate. Secondary endpoints were safety, survival, change in serum vascular endothelial growth factor (VEGF)/soluble VEGF receptor‐2 (sVEGFR2), and the activity of sunitinib in patients who developed disease progression while receiving placebo. A total of 38 eligible patients per treatment arm were required to select better therapy with 90% probability (α = .05). RESULTS: A total of 54 eligible patients were randomized to either the sunitinib arm (26 patients) or the placebo arm (28 patients). The median number of cycles received was 2 cycles per treatment arm. The most common grade 3 to 4 adverse events (graded according to version 3.0 of the National Cancer Institute Common Terminology Criteria for Adverse Events) among patients receiving sunitinib were thrombocytopenia, diarrhea, mucositis, fatigue, and hypertension. There were no grade 3 or 4 adverse events noted among > 5% of patients receiving placebo. The 6‐month progression rate was 72% versus 64%. The median progression‐free survival (PFS) was 2.9 months (range, 0.5 months‐32.5 months) versus 2.7 months (range, 0.8 months −65 months) for the sunitinib versus placebo arms, respectively. Patients receiving placebo were found to have no changes in their serum VEGF/sVEGFR2 levels over time. Patients treated with sunitinib had no significant change in their VEGF level, but the sVEGFR2 level significantly decreased after cycles 1 and 2 ( P  < .0001) and at the time of disease progression ( P  = .0002). A baseline VEGF level that was at or greater than the median was found to be correlated with a longer PFS. Sixteen patients who were receiving placebo received sunitinib at the time of disease progression, with the best responses being 1 partial response (6.3%), 6 cases of stable disease (37.5%), and 5 cases of progressive disease (31.3%); 4 patients were not evaluable for response. The median PFS was 3.7 months (range, 0.1 months‐22 months). CONCLUSIONS: The current multicenter study was limited by premature closure and a small sample size. Maintenance sunitinib did not appear to improve the 6‐month progression rate. Open‐label sunitinib was found to have only modest activity. The sVEGFR2 level decreased among patients receiving sunitinib. Cancer 2014;120:692–701 . © 2013 American Cancer Society . Abstract : The authors investigated the role of maintenance sunitinib in patients with advanced urothelial carcinoma. Maintenance sunitinib did not improve the 6‐month progression rate and appeared to have only modest activity.